An ANALYSIS OF STUDENTS' ERROR IN USING PASSIVE VOICE - Yoga Widiadnya, I Gusti Ngurah Bagus; Lestari, I Gusti Ayu Agung Yuni (Jurnal Ilmiah Bina Bahasa, 2021)
Abstract: This research aimed to find out the errors made by the tenth-grade students of Smk Nusa Dua especially first grade students of hotel accommodation program in using passive voice. This purposed of this research is to find out the types of errors. The researcher used Dulays’ theory to find the types of error. Furthermore, the researcher used descriptive qualitative research design. To get the sample, the researcher used cluster sampling technique. The researcher took 45 students as a sample from class 10 AP2. To analysis the data, the researcher gave a test about passive voice of simple present tense. There were totally 352 errors created by the students. Those errors derived from omission with 21 errors, addition with 67 errors, misformation with 253 errors and misordering with 11 errors.